Slaughter weight, sex and age effects on beef shear force and tenderness - Lucero Borja, Jorge Omar; Pouzo, Laura Beatriz; de la Torre, M.S.; Langman, Leandro Ezequiel; Carduza, Fernando Jose; Corva, Pablo Marcelo; Santini, Francisco Jose; Pavan, Enrique (Elsevier, 2019)
In Argentina, beef cattle prices decrease as slaughter weight increases regardless of animal age or carcass maturity, and this decrease is significantly greater in heifers (15%) than in steers (5%). The objectives of the present study were to (1) determine whether shear force and tenderness differ between heifers of different slaughter weight, and between heifers, steers and cull cows of similar slaughter weight; (2) evaluate whether such differences, if any, could be overcome by extending beef aging period; and (3) understand the main causes of such differences in beef shear force and tenderness. Meat from heavy heifers (H-HEIFER, 381–420 kg BW) was compared to meat from light heifers (L-HEIFER, 300–340 kg BW), steers (STEER, 391–450 kg BW) or cull cows of similar weight (COW). At slaughter, carcass characteristics were determined and Longissimus thoracis (LM) and Gluteus medius (GM) muscle samples collected for shear force determination. Total and insoluble collagen, sarcomere length and intact troponin-T content, and sensory panel scores, were evaluated for LM. Aging effect was evaluated for shear force and sensory panel scores. Irrespective of muscle or aging period, increasing heifer slaughter weight did not impact negatively on beef shear force or tenderness levels; heifers and steers of similar slaughter weight had similar beef shear force and tenderness levels; whereas heifer beef was more tender (P<0.05) than that from cow of similar slaughter weight. Tenderness differences were not overcome by extending the aging period. Based on a principal component analysis, shear force and tenderness differences appear to be associated to the variation in chilling rate and sarcomere length.